2015
DOI: 10.5194/isprsarchives-xl-7-w3-797-2015
|View full text |Cite
|
Sign up to set email alerts
|

Fire Monitoring - The use of medium resolution satellites (AVHRR, MODIS, TET) for long time series processing and the implementation in User Driven Applications and Services

Abstract: ABSTRACT:This paper introduces fire monitoring works of two different projects, namely TIMELINE (TIMe Series Processing of Medium Resolution Earth Observation Data assessing Long -Term Dynamics In our Natural Environment) and PHAROS (Project on a Multi-Hazard Open Platform for Satellite Based Downstream Services). It describes the evolution from algorithm development from in applied research to the implementation in user driven applications and systems. Concerning TIMELINE, the focus of the work lies on hot sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…2017, 9, 30 3 of 22 An extensive round robin approach which tested and validated different methods and thresholds has shown that the contextual algorithm performs best for hotspot detection with AVHRR [70]. Therefore, a further enhancement of the contextual algorithm of Giglio et al [61] is used for final implementation (cf.…”
Section: Methods For Active Fire Detectionmentioning
confidence: 99%
“…2017, 9, 30 3 of 22 An extensive round robin approach which tested and validated different methods and thresholds has shown that the contextual algorithm performs best for hotspot detection with AVHRR [70]. Therefore, a further enhancement of the contextual algorithm of Giglio et al [61] is used for final implementation (cf.…”
Section: Methods For Active Fire Detectionmentioning
confidence: 99%
“…Fire point recognition methods such as image enhancement method, threshold method (single threshold method, multi threshold method and dynamic threshold method), NDVI index method [11][12][13]. Fuchs et al [19] were the first to use the Threshold Method based on mid-infrared and far-infrared channels to monitor fires. In this method, the discrimination threshold is set based on the surface temperature rise and the abnormal brightness temperature of mid-infrared and far-infrared channels when a wildfire occurs.…”
Section: Introductionmentioning
confidence: 99%
“…In general,for early detection of forest fires,it is necessary to use satellite data with at least medium spatial resolution (-1 km)and high temporal resolution (Schroeder et al (2008), Fuchs et al (2015)).…”
Section: Introductionmentioning
confidence: 99%